The protective effects of dietary resistant starch against post-antibiotic bone loss in meat ducks associated with the recovery of caecal microbiota dysbiosis - Y.Y. Huang; S.M. Qin; M.T. Nguyen; W. Chen; X.M. Si; Y.Q. Huang; H.Y. Zhang (Poultry Science)
Compromised bone quality increases the risk of fractures in domesticate birds, resulting in pain and altered behaviour. Although dietary resistant starch (RS) supplementation show promise for improving inferior bone mass, the diet-mediated gut microbiota alterations as a potential mechanism underlying RS positive roles in bone remains uncertain. With a post-antibiotic model and faecal microbiota transplantation (FMT), this study investigated the effects of a RS diet on antibiotic-induced bone loss and gut microbial composition in meat ducks. Ducklings were assigned to 4 treatments with 6 replicate pens until 21 d, including the control group (Ctrl, feeding a basal diet) and the RS-fed group, and post-antibiotic treatment following the gavage of phosphate-buffered saline (Post-anti-PBS) or faecal microbiota transplantation (Post-anti-FMT). The RS diet increased the proportion of Firmicutes, improved intestinal integrity, and reduced inflammation-induced bone resorption, all of which contributed to an increase in tibial bone volume (P < 0.05). Post-antibiotic treatment was found to reduce tibial quality by stimulating bone resorption and inhibiting bone formation, accompanied by gut microbiota dysbiosis, increased intestinal permeability (P = 0.059), and inflammatory flare compared to control birds. FMT from RS-fed ducks into the antibiotic-treated birds reversed bone loss by primarily blocking osteoclastic frequency and activity. Furthermore, FMT increased the ratio of Firmicutes to Bacteroidetes (P < 0.05) and suppressed the release of pro-osteoclastogenic cytokines such as tumour necrosis factor-α (P = 0.062) and interleukin-1β (P < 0.05) in the bone marrow. These results demonstrated the involvement of gut microbiota in improving bone quality of meat ducks by RS, and FMT of RS-fed birds corrected the imbalance of ceca microbiota and attenuated bone loss in meat ducks with enhanced bone resorption.